The Spanish Foreign Legion in the Spanish Civil War, 1936 - Álvarez, Jose E. (Book collections on Project MUSE., 2016)
"In 1936, the Spanish Foreign Legion was the best equipped and most thoroughly trained and battle-tested unit in the Spanish Army. With its fearsome reputation for brutality and savagery, the Legion was not only critical to the eventual victory of Franco and the Nationalists, but was also a powerful propaganda tool the Nationalists used to intimidate and terrorize their enemies. Drawing upon Spanish military archival sources, the Legion's own diary of operations, and relevant secondary sources, Álvarez recounts the pivotal role played by the Spanish Foreign Legion in the initial months of the Spanish Civil War."--